Adaptation of the Intelligence Structure Test, Latvian version: psychometric properties - Jokste, Inese; Trups-Kalne, Ingrida; Lubenko, Jelena; Millere, Inga; Kolesnikova, Jelena (Frontiers in Psychology, 2024)
The Intelligence Structure Test (IST-2000R) is created to measure reasoning abilities and knowledge through verbal, numerical, and figural domains. The qualities of IST-2000R have shown its potential to be adapted and standardized in a Latvian sample to be used in psychological evaluation and research, thus satisfying the need for reliable measurement. The aim of this study was to investigate the psychometric properties of the Latvian version of IST-2000R. The adaptation sample consisted of 1,017 participants aged 15–65 (M = 31.8; SD = 10.94), of whom 36% were male. Participants were tested using the supervised offline administration mode (exploro.lv). The Ethics Committee of Riga Stradins University (RSU), Riga, Latvia, approved the study. The data show that the psychometric properties of the Latvian version of IST-2000R are in line with scientific norms. Thus, the test is considered to be reliable and may be used for psychological evaluation and research.